Antioxydant Extract of Endophytic Fungi Fusarium oxysporum LBKURCC41 - Marlinda, Sri; Teruna, Hilwan Yuda; Pratiwi, Nova Wahyu; Ardhi, Aulia; Saryono, Saryono (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2019)
Fusarium oxysporum LBKURCC41 is one of endophyte fungi which is able to produce secondary metabolites. The purpose of this research was to discover an antioxidant agent from F. oxysporum LBKURCC41extract that was fermented in Huang medium for 15 d with of corn and potato with particle size of 80 mesh as carbon sources. The ethyl acetate extract from the cultured medium showed four dominant component with retentiont time of 3.24, 3.44, 17.02 and 18.889 min. The F. oxysporum LBKURCC41 extract containing compounds with functional group O-H, C-H and C-O, and it had a IC50 value of 435,157±12,009a.